1987
DOI: 10.1007/bf02556492
|View full text |Cite
|
Sign up to set email alerts
|

The role of preoperative colonoscopy in colorectal cancer

Abstract: Routine preoperative colonoscopy has been recommended for those patients with the diagnosis of colorectal cancer to identify synchronous polyps and/or cancers which might otherwise be undetected on barium enema or at the time of operation. It has been suggested that this approach may alter surgical therapy or follow-up. The charts of 98 patients who underwent preoperative colonoscopy solely for the purpose of detecting additional polyps or cancers prior to open surgical resection for colorectal cancer were ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…The stage of cancer at the time of diagnosis was similar in our study to that reported else where [22]. Nearly 40% of all cancers were in metastatic stages at the time of diagnosis.…”
Section: Discussionsupporting
confidence: 78%
“…The stage of cancer at the time of diagnosis was similar in our study to that reported else where [22]. Nearly 40% of all cancers were in metastatic stages at the time of diagnosis.…”
Section: Discussionsupporting
confidence: 78%
“…Another study showed that 69% of synchronous cancers were overlooked by intraoperative palpation, which also happened in our study (30). All these studies emphasize the importance and the benefits of preoperative colonic evaluation, which was also recommended in several reports (3,7,8), but preoperative evaluation is not standard procedure everywhere at the present time. In a retrospective study of 534 patients by Achiam et al (5), 78% of the patients did not have preoperative examinations of the entire colon, of which only 23% were due to obstructing cancers.…”
Section: Discussionsupporting
confidence: 45%
“…Synchronous lesions have been described numerous times in the literature, with varying incidences of 2% to 11% for cancers and 12% to 58% for polyps (1)(2)(3)(4)(5)(6). Thus, the widespread recommendation for full colonic evaluation preoperatively with conventional colonoscopy (CC) (3,7,8) seems only sensible and is aimed at reducing morbidity and mortality.…”
mentioning
confidence: 96%
“…It is therefore essential to ascertain preoperatively whether a second lesion exists. Although other workers have reported that the rate of a successful total colonoscopy from anus to cecum was 75% on the average [15], colonoscopy is currently regarded as the most accurate method for the diagnosis of colorectal carcinoma [12,16]. The predominance of colonoscopy over DCBE has also been recognized [6].…”
Section: Discussionmentioning
confidence: 97%